The effects of a brief hope intervention on decision‐making in chronic kidney disease patients: A study protocol for a randomized controlled trial. (10th October 2020) - Chan, Kitty; Wong, Frances; Tam, Suet Lai; Kwok, Ching Ping; Fung, Yuen Ping; Wong, Ping Nam
Abstract: Aims: This study describes the study protocol of a manualized brief hope intervention that is based on the theoretical proposition – hope theory. Background: Patients with stage 5 chronic kidney disease often had decisional regret when facing the tension of treatment alternatives between dialysis initiation and palliative care. Hope has been found to account for therapeutic changes in clients with depressive symptoms, heightens positive expectations, and striving to accomplish chosen goals. Nevertheless, little is known about the effect of hope on decisional conflict and its influences to the quality of life in these chronic kidney disease patients. Design: This study is a single‐blinded, randomized controlled trial. Methods: Participants will be recruited from a regional hospital (approved in April 2018). They will be randomly assigned in equal numbers to either the brief hope intervention or the control arm on completion of the baseline assessment on the possible need of dialysis initiation. Participants in the intervention group will receive the pre‐dialysis education and a 4‐week Brief Hope Intervention [consisting of four sessions at weekly intervals (two face‐to‐face sessions and two telephone follow‐up sessions in between)], while those allocated to the control arm will receive the renal education and social chats. Outcome measures will be carried out prior to the intervention (baseline), immediately, and 1 month after the intervention. These consist of the hope level, decisional conflict, and quality of life. Healthcare resources use data will be reported. Impact: The study results have the potential to add scientific evidence to the research‐tested programme when developing renal services integral to multimodal care management to optimize decision‐making and attain better health outcomes. 摘要: 目的: 本研究描述了一个基于理论命题‐希望理论的可操作性短期干预的研究方案。 背景: 慢性肾脏疾病5期患者在面对透析和姑息治疗较为紧张, 因此, 一般情况下, 其都会后悔在这个过程中所作的决定。研究发现, 希望可以对抑郁症患者的治疗产生影响, 增强其积极的期望, 致使其努力实现选定的目标。然而, 人们并未充分了解希望在决策冲突中的作用以及其对慢性肾病患者生活质量的影响。 设计: 本研究为单盲、随机对照试验。 方法: 将从地区医院招募参与者(2018年4月获得批准)。如果已经完成透析用基线评估, 所有参与者都将随机分配给短期希望干预组或对照组, 且两组的人数相同。干预组的参与者接受透析前教育和为期4周的简短希望干预【包括每周4次的讨论(两次面对面讨论和两次电话随访)】, 而控制组的参与者将接受肾脏知识教育, 并将参与社交聊天。需要分别在干预前(基线)、干预时和干预后1个月对结果进行测量。具体内容包括希望水平、决策冲突和生活质量。此外, 需要对医疗资源的使用数据进行报告。 影响: 本研究结果可能用作经研究验证的项目的科学证据, 以便开发多种模式的肾脏护理及管理服务, 最终优化决策并确保患者获得更好的健康结果。